Pillared clays as "green chemstry" catalysts for wastewater treatment - Baloyi, Siwela Jeffrey (My University, 2019)
In this study, the CWAO (catalytic wet air oxidation) of phenol was studied in a batch and plug-flow reactors operated in continuous mode, using a highly active and stable heterogeneous catalysts. Three pillared clay-based heterogeneous catalysts, Al/Zr-PILCs (aluminium/zirconia pillared interlayered clays), Al/Fe-PILCs (aluminium/iron pillared interlayered clays) and Al/Cr-PILCs (aluminium/chromium zirconia pillared interlayered clays) were synthesized using ultrasonic treatment method and screened for their efficiency in removing phenol in aqueous medium in a batch autoclave reactor. The method of hydrolysis and ion exchange were successfully achieved by direct addition of the clay into the pillaring solution using ultrasonic treatment both during the formation of the pillaring solution and in the intercalation process, respectively. The preparation method used in this study significantly reduced the synthesis time and the water consumption required compared to conventional method discussed in the literature, indicating advantages of potential scale-up of the pillared clay preparation. Calcination of the synthesized pillared clay catalysts at 500 °C for 120 minutes yielded optimum physical properties with BET (Brunauer–Emmett–Teller) surface area of 180 - 230 m2/g and basal spacing of 1.50 - 1.92 nm and with good thermal stability. All catalysts achieved a complete removal of phenol and above 80% TOC conversion after 120 min in aqueous solution under mild reaction conditions of 100 °C and 10 bar. Of the catalysts, screened Al/ZrPILCs catalyst, especially with Al/Zr ratio of 3:1 was the most active catalyst in terms of phenol removal, TOC conversion and stability. For practical purposes, Al/Zr-PILCs as the best selected PILCs (pillared interlayered clays) catalytic powder was fixed on a monolithic substrate. Since the use of monolithic catalysts to the oxidation of phenol in wastewaters can minimize the pressure drop in the flow reactor. The cordierite monoliths coated with Al/Zr pillared bentonite clay powder were synthesized, characterized and tested in phenol oxidation. The BET specific surface area and mean pore size of the monolithic catalysts obtained by N2 adsorption–desorption isotherm studies shows that the catalyst are mesoporous by showing type IV adsorption isotherms. The HRSEM (high resolution scanning electron microscopy) characterization results confirmed the active components were well deposited on the channel walls and the washcoat is observed in all the corners of the washcoated monolith cross section, while the EDX (energy dispersive X-ray spectrometer) revealed the presence of the Zr and Fe elements in the cordierite monolithic catalyst walls. Ultrasound experiments used to estimate the coating adherence show that the washcoated Al/Zr pillared bentonite powder is well anchored on the cordierite. Kinetics of CWAO of phenol was studied over powder Al/Zr-PILCs and monolithic catalyst using a batch autoclave reactor and flow reactor, respectively. During the CWAO of phenol reaction, aromatic ring intermediates (p-benzoquinone, catechol acid and hydroquinone) and short chain carboxylic acids (oxalic acid, maleic acid, formic acid, acetic acid and malonic acid) were identified. Kinetic parameters of the model that describes the formation and oxidation of intermediate aromatic compounds and short chain carboxylic acids were determined. The proposed CWAO of phenol kinetic model account for internal and external diffusion limitations, assuming the pseudo-first order reaction. Therefore, the proposed approach can be used for scaling-up the CWAO of phenol in plug flow reactor. The reaction pathway for the CWAO of phenol was proposed. These findings show that the novel Al/Zr-PILCs monolithic catalyst have a great potential for application in CWAO of phenol, since the materials used in the process are inexpensive, abundant and require minimal modifications. To best of our knowledge, the application of Al/Zr-PILCs/cordierite monolith catalyst for this reaction has not been previously reported
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy January 2019
Keywords: Green chemistry; Environmental chemistry